2012
DOI: 10.1007/s00271-012-0361-1
|View full text |Cite
|
Sign up to set email alerts
|

Pond management and water quality for drip irrigation in Mediterranean intensive horticultural systems

Abstract: The influence of pond management on water quality for drip-irrigated crops was studied throughout a field survey and a mesocosm experiment. Water sources were pooled into two groups: ground or surface water (GW/SW) and recycled wastewater. Pond covering, which was limited to about a quarter of them, improved water quality by reducing phytoplankton biomass. However, biocide applications and pond dredging were ineffective at improving in-pond water quality. Dredging did not reduce the concentrations of planktoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…The main argument put forward by growers for applying copper sulfate to their ponds was the eradication of submerged vegetation [13]. However, recent studies have shown that this management practice had negative consequences on water quality for irrigation, since it significantly increased the levels of particles suspended in water as compared to those in vegetated untreated ponds, thus increasing the plugging potential of emitters of the drip irrigation systems mostly used in the greenhouse horticulture [15]. Therefore, despite the remarkable natural copper-buffering capacity we have detected for pond water in the area studied, diverse agronomical, environmental (this study, [17,18]) and human health (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main argument put forward by growers for applying copper sulfate to their ponds was the eradication of submerged vegetation [13]. However, recent studies have shown that this management practice had negative consequences on water quality for irrigation, since it significantly increased the levels of particles suspended in water as compared to those in vegetated untreated ponds, thus increasing the plugging potential of emitters of the drip irrigation systems mostly used in the greenhouse horticulture [15]. Therefore, despite the remarkable natural copper-buffering capacity we have detected for pond water in the area studied, diverse agronomical, environmental (this study, [17,18]) and human health (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of both high Cu doses and alkalinity has resulted in vast accumulation of Cu in pond sediments, averaging up to 2.2 g Cu/kg dry sediment . Although pH in these ponds is normally alkaline (8.2) , such that most sedimentary Cu must be scarcely bioavailable, these extremely high Cu levels might eventually jeopardize associated species. Recent studies indeed have shown that untreated irrigation ponds with submerged aquatic vegetation harbored more diverse macroinvertebrate assemblages as well as denser and healthier subpopulations of the endangered endemic Mediterranean toothcarp, Aphanius iberus (Valenciennes, 1846), than those treated with copper sulfate .…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with the pond owners revealed that the average flushing rate was <22 days in ART ponds (Juan et al ., ). Intensive and destructive management practices such as periodic biocide treatment and dredging of submerged vegetation are common (Juan et al ., ; Bonachela et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…The influence of management practices on biodiversity has recently drawn the attention of conservationists, who attempt to understand the functioning of anthropogenically disturbed ecosystems (Lemmens et al ., ; Chester & Robson, ; Usio et al ., ). This is because the degree of manipulation and the management regime of ponds are both highly related to use and construction type (Casas et al ., ,b; Juan et al ., ; Bonachela et al ., ), with strong implication for their α‐, β‐ and γ‐diversities (Fuentes‐Rodríguez et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…En particular, las plantas acuáticas sumergidas, en la actualidad mayoritariamente denostadas por los agricultores, tienen capacidades para aclarar el agua, mejorando su calidad para sistemas de riego localizado (Bonachela et al, 2013;Juan, Casas, Elorrieta, Bonachela, Gallego, Fuentes-Rodríguez y Fenoy, 2014), y, a su vez, crean hábitats que sirven de refugio y proveen de alimento a numerosas especies de macroinvertebrados bentónicos (Fuentes-Rodríguez et al, 2013).…”
Section: Introductionunclassified